2022
DOI: 10.48550/arxiv.2208.03999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating chemically homogeneous evolution in stellar binaries: Electromagnetic implications -- Ionizing photons, SLSN-I, GRB, Ic-BL

Abstract: We investigate the occurrence of rapid rotation induced Chemically Homogeneous Evolution (CHE) caused by strong tides and mass accretion in binary systems. Using , we derive a relation for the minimum initial angular frequency required by a single star to experience CHE. This is then extended to derive a similar relation for accretion induced CHE in binaries by generalizing the analytical relation in Packet (1981). In contrast to traditionally assumed 5-10 per cent accretion of initial mass for spinning up an … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…The above properties distinguish the jittering jets explosion mechanism from other jet-driven explosion mechanisms (e.g., LeBlanc & Wilson 1970;Khokhlov et al 1999;Aloy et al 2000;MacFadyen et al 2001;Burrows et al 2007;Barkov & Komissarov 2008;Wheeler et al 2008;Maeda et al 2012;López-Cámara et al 2013;Bromberg & Tchekhovskoy 2016;Nishimura et al 2017;Sobacchi et al 2017;Grimmett et al 2021;Gottlieb et al 2022aGottlieb et al , 2022cGhodla et al 2022;Perley et al 2022). In particular, these mechanisms assume a rapidly rotating precollapse core, something that is not required in the jittering jets explosion mechanism.…”
Section: The Definition Of the Mechanismmentioning
confidence: 95%
“…The above properties distinguish the jittering jets explosion mechanism from other jet-driven explosion mechanisms (e.g., LeBlanc & Wilson 1970;Khokhlov et al 1999;Aloy et al 2000;MacFadyen et al 2001;Burrows et al 2007;Barkov & Komissarov 2008;Wheeler et al 2008;Maeda et al 2012;López-Cámara et al 2013;Bromberg & Tchekhovskoy 2016;Nishimura et al 2017;Sobacchi et al 2017;Grimmett et al 2021;Gottlieb et al 2022aGottlieb et al , 2022cGhodla et al 2022;Perley et al 2022). In particular, these mechanisms assume a rapidly rotating precollapse core, something that is not required in the jittering jets explosion mechanism.…”
Section: The Definition Of the Mechanismmentioning
confidence: 95%
“…Pols et al 1991), in extreme cases this could lead to unusual evolution (such as homogeneous or quasi-homogeneous evolution, e.g. Eldridge et al 2011;Mandel & de Mink 2016;Ghodla et al 2022), or they can be polluted by winds from a stripped-envelope companion (Clark et al 2014). It has also been suggested that secondaries might appear inflated and red for a short time (∼1000 yr) after the supernova of a companion, as a result of the impact of the primary ejecta (Liu et al 2015;Hirai et al 2018;Ogata et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Upcoming multi-object spectrographs and integral field units such as WEAVE (WHT Enhanced Area Velocity Explorer, Dalton et al 2014) and 4MOST (4-metre Multi-Object Spectrograph Telescope, de Jong et al 2014) also offer new opportunities to characterise candidates in the vicinity of supernova remnants and young neutron stars, through the identification of stars with high radial velocities, high rotational velocities or unusual chemical abundances, which may be indicative of past binary interactions (e.g. Clark et al 2014;Ghodla et al 2022).…”
Section: Introductionmentioning
confidence: 99%